The good life of teaching : an ethics of professional practice - Higgins, Chris, 1967- (Malden, MA : Wiley-Blackwell, 2011)
"The Good Life of Teaching extends the recent revival of virtue ethics to professional ethics and the philosophy of teaching. It connects long-standing philosophical questions about work and human growth to questions about teacher motivation, identity, and development. Makes a significant contribution to the philosophy of teaching and also offers new insights into virtue theory and professional ethics. Offers fresh and detailed readings of major figures in ethics, including Alasdair MacIntyre, Charles Taylor, and Bernard Williams and the practical philosophies of Hannah Arendt, John Dewey and Hans-Georg Gadamer. Provides illustrations to assist the reader in visualizing major points, and integrates sources such as film, literature, and teaching memoirs to exemplify arguments in an engaging and accessible way. Presents a compelling vision of teaching as a reflective practice showing how this requires us to prepare teachers differently "--
Cover; Contents; Title; Copyright; Dedication; Foreword; Acknowledgements; Introduction: Why We Need a Virtue Ethics of Teaching; Part I: The Virtues of Vocation: From Moral Professionalism to Practical Ethics; Chapter 1: Work and Flourishing: Williams' Critique of Morality and its Implications for Professional Ethics; Introduction; Retrieving Socrates' Question; Modern Moral Myopia; What do Moral Agents Want?; From Moral Professionalism to Professional Ethics; Notes; Chapter 2: Worlds of Practice: MacIntyre's Challenge to Applied Ethics; Introduction.
"Originally published as volume 44, issues 2 and 3 of The journal of philosophy of education"--Title page verso.
Includes bibliographical references (pages 283-303) and index.
Print version record.
Keywords: Teaching -- Moral and ethical aspects; Education -- Moral and ethical aspects; Teaching -- Philosophy; Education -- Philosophy; PHILOSOPHY -- History & Surveys -- General; EDUCATION -- Teaching Methods & Materials -- General; Education -- Moral and ethical aspects; Education -- Philosophy; Teaching -- Moral and ethical aspects; Teaching -- Philosophy; Electronic books